A new application of humic substances: Activation of supports for invertase immobilization - Rosa, André Henrique [UNESP]; Vicente, A. A. [UNESP]; Rocha, J. C. [UNESP]; Trevisan, H. C. [UNESP] (Springer Nature, 2000)
Invertase was immobilized on aminopropyl silica (APTS-SiO2) activated with humic substances (APTS-SiO2-HS) and on aminopropyl silica activated with glutaraldehyde (APTS-SiO2-GA). The resulting activity of both systems was compared. Humic substances (HS) used for the activation of the silica were extracted from soil of Cananéia, São Paulo State, Brazil, according to the procedure recommended by the International Humic Substances Society. Activity was determined by measuring the rate of formation of reduced sugars using the reaction with dinitrosalicylic acid (DNS). The amount of HS bound on the APTS-SiO2 was equal to 50 mg. The maximum amount of invertase immobilized on APTS-SiO2-HS was 15200 U/g while in the system APTS-SiO2-GA it was 13400 U/g. The experimental enzymatic activity was 3700 and 3300 U/g, for the systems APTS-SiO2-HS and APTS-SiO2-GA, respectively. Considering the increased amount and activity of immobilized enzyme compared with the glutaraldehyde method, it was concluded that this technique opens a new perspective in the preparation of supports for enzyme immobilization employing humic substances. © Springer-Verlag 2000.
Keywords: aminopropyl silica gel; beta fructofuranosidase; chelating agent; dyes, reagents, indicators, markers and buffers; glutaraldehyde; glycosidase; immobilized enzyme; silicon dioxide; chemistry; humic substance; infrared spectroscopy; isolation and purification; beta-Fructofuranosidase; Chelating Agents; Enzymes, Immobilized; Glutaral; Glycoside Hydrolases; Humic Substances; Indicators and Reagents; Silicon Dioxide; Spectroscopy, Fourier Transform Infrared